A model of consensus formation for reconciling nursing's disciplinary matrix - Dobratz, Marjorie C. (Nursing philosophy, 2010)
With questions raised as to whether or not nursing knowledge should be developed from extant conceptual/theoretical models or from practice-based environments, this paper utilizes Kuhn's disciplinary matrix and Laudan's model of consensus formation to explore the changing nature of the discipline's structural matrix. Kuhn's notion that a discipline's structural matrix includes symbolic generalizations, models and exemplars, and Laudan's view that a maturing discipline embraces factual, methodological, and axiological (goals and aims) knowledge, and that context and discourse are also involved in advancing a discipline is described as a means for reconciling the source of nursing knowledge. This paper posits that shared axiological goals connect both theorists and practitioners, and resolve potential conflicts as to viable sources of nursing knowledge. Through shared goals that include humanization, meaning, quality of life, caring, consciousness, transcendence, and presence, which bridge both theoretical and practice approaches, nursing's charge to contribute to the good of society is fulfilled.